Low-dose adefovir dipivoxil–induced hypophosphatemia osteomalacia in five chronic hepatitis B virus–infected patients. Is low-dose adefovir dipivoxil–induced nephrotoxicity completely reversible? - Qian YY; Dai ZJ; Ruan LY; Pan YJ; Jin J; Shi MT; Zhu YX; Wu CM (Dove Medical Press, 2019)
Yan-Ying Qian, Zhi-Juan Dai, Lu-Ya Ruan, You-Jin Pan, Jian Jin, Meng-Te Shi, Yao-Xin Zhu, Chao-Ming WuDepartment of Endocrinology, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang 325027, People’s Republic of ChinaAbstract: Adefovir dipivoxil (ADV) is one of the most important nucleostide analogues currently in use for the treatment of chronic hepatitis B virus (HBV) infection. Low-dose ADV-induced nephrotoxicity in most cases was reported to be reversible after the discontinuation of ADV or by decreasing the dose of ADV. In our study, we have 5 documented cases of low-dose ADV-induced hypophosphatemia osteomalacia with or without Fanconi syndrome which were diagnosed in our hospital between 2010 and 2017. Three patients were observed to have a full recovery after the discontinuation of ADV. Two patients had persistently elevated urine β2-microglobulin levels and out of these two patients, one patient had persistent hypophosphatemia after the cessation of ADV. These cases illustrated that the use of low-dose ADV increased the risk of nephrotoxicity, and in some patients, low-dose ADV-induced nephrotoxicity was not completely reversible. Patients of East Asian origin, especially those with a low body mass index, were prone to a relatively higher risk of developing low-dose ADV-induced nephrotoxicity; therefore, it was worth paying attention to the side effects caused by low-dose ADV.Keywords: hypophosphatemia osteomalacia, chronic hepatitis B virus, adefovir dipivoxil